Pengakuan dan Ketidakadilan: Analisis Wacana UU Anti-Deforestasi Melalui Lensa Axel Honneth bagi Petani Sawit - Ikhsan , Ikhsan; Hajad, Vellayati; Yanda, Safril; Syahroni, Faez; Setiawan, Deni (Indonesian Journal Publisher, 2025)
This paper attempts to analyze the impact of Anti-Deforestation Laws, specifically the European Union Zero Deforestation Regulation (EUDR), on smallholder oil palm farmers in Indonesia through the lens of Axel Honneth’s recognition theory. This paper aims to understand how the policy creates structural injustice and ignores the realities of smallholder farmers’ lives. The method used is critical discourse analysis, which highlights how the language and ideology in this policy shape global perceptions of sustainability. The results show that the policies contained in the EUDR function as tools for environmental conservation and reproduce a global power hierarchy that benefits developed countries. Thus, the bargaining position of smallholder oil palm farmers in Indonesia is being worsened, social exclusion is being created, and a global power hierarchy is being reproduced. This paper concludes that the Indonesian Government can formulate inclusive and responsive policies to farmers’ needs. The policy recommendations include providing access to land legality, training programs, and dialogue between the Government and farmers so that the injustices generated by the EUDR can be minimized, creating a more equitable and sustainable agricultural system in Indonesia.